1982
DOI: 10.1007/bf00294971
|View full text |Cite
|
Sign up to set email alerts
|

Regional and temporal changes in the pattern of X-chromosome replication during the early post-implantation development of the female mouse

Abstract: We have made a detailed study of the X-chromosome replication pattern during the period when X-inactivation is occurring in the mouse embryo. Our observations show unequivocal regionalization of the embryo with respect to the temporal X-chromosome. The switch from isocyclic to allocyclic replication occurs in the embryonic ectoderm at approximately 6 days of development and is random with respect to parental origin of the X-chromosome. In the extra-embryonic tissues, however, the switch to allocyclic replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 26 publications
4
107
0
Order By: Relevance
“…However, in the extraembryonic tissues of some placental mammals, such as rodents, XCI takes place in an "imprinted" manner such that the paternal X (Xp) is always silenced (Takagi and Sasaki 1975). Earlier classical cytogenetics studies suggested that the paternal X only becomes inactivated at the blastocyst stage, accompanying cellular differentiation in the trophoectoderm and primitive endoderm (Takagi et al 1982). However, recent studies have revealed that the paternal X has already begun to inactivate by the eight-cell stage (Huynh and Lee 2003;Mak et al 2004;Okamoto et al 2004;Okamoto and Heard 2006) and this inactivation of Xp initiates following Xist RNA coating at the four-cell stage (Okamoto et al 2004(Okamoto et al , 2005.…”
Section: XCImentioning
confidence: 99%
“…However, in the extraembryonic tissues of some placental mammals, such as rodents, XCI takes place in an "imprinted" manner such that the paternal X (Xp) is always silenced (Takagi and Sasaki 1975). Earlier classical cytogenetics studies suggested that the paternal X only becomes inactivated at the blastocyst stage, accompanying cellular differentiation in the trophoectoderm and primitive endoderm (Takagi et al 1982). However, recent studies have revealed that the paternal X has already begun to inactivate by the eight-cell stage (Huynh and Lee 2003;Mak et al 2004;Okamoto et al 2004;Okamoto and Heard 2006) and this inactivation of Xp initiates following Xist RNA coating at the four-cell stage (Okamoto et al 2004(Okamoto et al , 2005.…”
Section: XCImentioning
confidence: 99%
“…The first wave occurs during preimplantation embryogenesis and is subject to imprinting, resulting in preferential inactivation of the paternal X (Xp) chromosome (1). Inactivity of the Xp is maintained in the trophectoderm of the blastocyst but is reversed in the inner cell mass (2,3), where a second wave of random XCI takes place, affecting either the Xp or the maternal X (Xm) chromosome (4,5). The initiation of this second wave of XCI is controlled by a key regulatory locus, the X-inactivation center (Xic), which monoallelically upregulates either the paternal or maternal allele of the noncoding Xist transcript, thus triggering XCI in cis during an early time window of differentiation [for review, see Heard and Disteche (6)].…”
mentioning
confidence: 99%
“…[144][145][146] Additionally, the Xi has been described, decades ago, to exhibit particular replication dynamics that clearly differ from those of the Xa and the autosomes. 147,148 Hence, the Xi is a particularly interesting example of epigenetic regulation of replication timing. Interesting, the process of facultative heterochromatinization undergone by the Xi and the concomitant changes in replication dynamics, have been proposed to be the most prominent example of what actually happens in many, less prominent, regions of the genome, making the study of the Xi replication dynamics even more relevant.…”
Section: Epigenetics and Dna Replication Timing In Mammalsmentioning
confidence: 99%